Biomarkers in predicting cardiovascular risk: new prospects of troponin I - A. V. Kontsevaya; A. О. Myrzamatova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2020)
Risk stratification is an important aspect of effective control of cardiovascular diseases. Risk scores based on conventional risk factors did not solve the stratification problem completely due to a number of factors. One way to increase the accuracy of predicting cardiovascular risk may be to supplement conventional scores with cardiovascular biomarkers. Cardiac troponins are the most reliable cardiovascular biomarkers in the diagnosis of acute myocardial infarction. However, recent studies have shown that they have the potential to use as an addition to cardiovascular risk stratification scores. Cardiac troponins meet the requirements for new biomarkers: cardiospecificity, prognostic value, change in levels in response to risk reduction actions, evidence value, economic efficiency. A large number of population studies demonstrate the association of elevated levels of cardiac troponin I with adverse cardiovascular events. To assess the prospects of supplementing conventional risk scores with new biomarkers, including troponin I, the study of the role of biomarkers in cardiovascular risk prediction in men and women of working age is started in Russia.